Analysis of factors affecting water pollution in the Jeruju river tributary in Palembang city: A cross-sectional study - Barikah Utami; Arie Wahyudi; Muhammad Prima Cakra Randana (Lentera Perawat, 2025)
Background: River water pollution is an increasing environmental problem in urban areas, including Palembang City. Based on 2024 monitoring data, the water quality of the Jeruju tributary indicated elevated levels of BOD and COD exceeding quality standards due to domestic and industrial waste. This condition poses a threat to public health and aquatic ecosystem balance. Objective: This study aimed to analyze the factors influencing river water pollution in the Jeruju tributary of Palembang City in 2025. Methods: This research employed an analytical survey design with a cross-sectional approach involving 99 respondents living around the Jeruju tributary. Samples were selected using a simple random sampling technique. Data were collected through a structured questionnaire and analyzed using Chi-Square tests and multivariate logistic regression. Results: The findings revealed that all independent variables were significantly associated with river water pollution (p < 0.05). The three dominant influencing factors were environmental sanitation (p = 0.072; Exp(B) = 0.279), drainage and water management (p = 0.084; Exp(B) = 0.267), and community participation (p = 0.124; Exp(B) = 0.200). Conclusion: River water pollution in the Jeruju tributary is influenced by environmental and behavioral factors. Improved sanitation, enhanced drainage systems, and active community participation play key roles in reducing pollution risk. Local governments and communities should collaborate to strengthen waste management systems, promote environmental education, and implement community-based policies to ensure sustainable river water quality.